P16INK4A Expression on Retinoblastoma at Mohammad Hoesin Hospital Palembang - Sri Tanty Fuji A Harahap; Ika Kartika; Rusdianto (Sriwijaya Journal of Ophthalmology, 2018)
ABSTRACT Background: Retinoblastoma is a malignant tumor with an average incidence of one case per 15,000-20,000 births. Retinoblastoma is associated with the presence of the Rb1 gene mutation which has role in preventing DNA replication. Various studies have linked the existence of p16INK4A as a CDK inhibitor that inhibits Cyclin D and CDK4 so that the activity of the Rb1 gene is inhibited. Objective: This study was conducted to identify p16INK4A expression on Retinoblastoma at Mohammad Hoesin Hospital. Methodology: A descriptive study used on the paraffin blocks of 14 cases Retinoblastoma in Mohammad Hoesin Hospital Palembang from January 2014- July2018. Histopathologic feature were examined with Hematoxylin- Eosin staining and immunohistochemical were examined with p16INK4A antibody. Data were analyzed using SPSS version23 to identify histopathological feature of p16INK4A expression in Retinoblastoma Results: Most retinoblastoma samples in this study were expressed in p16INK4A (92.86%). The degree of differentiation of retinoblastoma with the largest number at Mohammad Hoesin Hospital is moderately differentiated (57.14%). Retinoblastoma invasion of the optic nerve and sclera in the study at Mohammad Hoesin Hospital, respectively at 57.14% and 42.86%. Conclusion: Most retinoblastoma samples in this study were expressed in p16INK4A.